The Effect of the 1997 Financial Crisis on the Stability and Predictability on Beta of the Malaysian Stock Exchange, 1992-2005 - Chen, Yin Foo; Lai, Chong Yee; Song, Kuok Thong (INTI Publishing House Sdn. Bhd., 2006)
This paper is a study on the stability and predictive quality of beta before and after the financial crisis of August 1997. Single securities and portfolios randomly formed from samples of the Main and Second Board were investigated. The mean and risk class bands of both boards had shifted lower indicating greater emphasis was placed on firm specific risk after the crisis. Substantial stability was found for pre and post crisis betas for the period immediately after the crisis but divergence was evident when comparing over a longer period. Product moment and Spearman rank correlation coefficient indicated generally weak correlations for pie and post crisis betas meaning that pre crisis values were poor predictors of post crisis betas. Possible extensions of this paper could include varying the length of the estimation period, forming industry-based portfolios and investing the extent of the presence of the dual bull-bear betas.